EnBovinOs: Diseño de una red de ontologías en el dominio de las enfermedades bovinas - Ballesteros-Ricaurte, Javier Antonio; González-Amarillo, Ángela María; Cáceres-Castellanos, Gustavo (Revista Científica, 2017)
In the field of veterinary medicine, terminology management is not standardized, because different actors intervene, generating inconveniences in the information consultation and in the processes of information collection and diagnosis of diseases. This paper presents the process of developing the ontology network: specification of requirements, application of NeOn Methodology, reuse of ontological and not - ontological resources, applied to knowledge of diseases in cattle. For the process of development of the network of ontologies, we counted on the support of veterinary doctors, experts in Mastitis Bovina that contribute their knowledge; Using computer tools and technologies, taking into account that the development meets the characteristics and that the integration of the different resources is obtained EnBovinos. Applying different scenarios of the methodology, there are resources that can be reused and in the same way to deliver a network of ontologies that can be used in other projects